Mitigate+ at Climate Week NYC 2023: Wei Zhang to talk about the role of women in climate mitigation in food systems - CGIAR Initiative on Low-Emission Food Systems (2023)
What is the role of women in mitigating greenhouse gas emissions from food systems? How do we at the CGIAR Initiative on Low-Emission Food Systems support women’s leadership and strengthen social-technical innovation for women? Wei Zhang, co-lead of Mitigate+, will address the above questions in an interactive moderated dialogue at a side event of the Climate Week NYC 2023.